Homeless population: characterization and contextualization by census research - Anai Adario Hungaro; Aroldo Gavioli; Rosangela Christóphoro; Sônia Regina Marangoni; Renan Filipe Altrão; Ana Lúcia Rodrigues; Magda Lúcia Félix de Oliveira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze characteristics of homeless people and factors associated with living on the streets. Methods: a census-type sectional survey carried out between 2015 and 2018, in the municipality of Maringá-Paraná. A total of 701 homeless answered a structured questionnaire with sociodemographic data, living conditions, and drug use. We used Pearson's correlation test for the association analysis of the variables at a 95% confidence level. Results: men (90.7%) the average age of 37.7 years had been homeless for an average of 5.39 years. Most had little education (54.2%), and homelessness was due to drug use (47.2%) and family disagreements (38.9%). Conclusions: drug use and family disagreements were the main reasons for homelessness. Time on the street, gender, and drugs were associated with a negative correlation to be homeless; and age, mean daily income, the number of daily meals, having been in prison, and having an income source were associated with positive correlation.